Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/cancers12102942
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Risk Atypical Meningiomas According to Semantic and Radiomic Features

Abstract: Up to 60% of atypical meningiomas (World Health Organization (WHO) grade II) reoccur within 5 years after resection. However, no clear radiological criteria exist to identify tumors with higher risk of relapse. In this study, we aimed to assess the association of certain radiomic and semantic features of atypical meningiomas in MRI with tumor recurrence. We identified patients operated on primary atypical meningiomas in our department from 2007 to 2017. An analysis of 13 quantitatively defined radiomic and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…It works by extracting a large number of quantitative characteristics from a medical image and then analyses these features by means of a series of machine learning algorithms (11). Although the radiomics approach for the evaluation of meningiomas pertaining to tumor grades and histological subtypes had recently been reported (12)(13)(14)(15), models for predicting clinical outcomes in overall meningiomas are still rare (10,16). Among the machine learning techniques, several studies had reported that support vector machine (SVM) classifiers offer excellent results in the classification and segmentation in brain tumors (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…It works by extracting a large number of quantitative characteristics from a medical image and then analyses these features by means of a series of machine learning algorithms (11). Although the radiomics approach for the evaluation of meningiomas pertaining to tumor grades and histological subtypes had recently been reported (12)(13)(14)(15), models for predicting clinical outcomes in overall meningiomas are still rare (10,16). Among the machine learning techniques, several studies had reported that support vector machine (SVM) classifiers offer excellent results in the classification and segmentation in brain tumors (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…This was not the first time for cyst formation to be scrutinized. In a previous study, cyst formation was the only feature selected among 13 radiomic and 11 visually accessible features for the identification of high-risk atypical meningiomas ( 34 ). Another previous study ( 8 ) showed that although there was no significant difference in the cystic component or necrosis between DMG-M and DMG-W tumors, there was a higher ratio of cystic components or necrosis of DMG-M (62.5%) compared to DMG-M (33.3%).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to substantial overlap in the regional ADCs for whole slices or whole brains that might lead to a lack of significant differences in texture features. Recent advances combined ADC metrics and texture features to perform classification for high-risk atypical meningiomas (35). Compared to ADC metrics that showed significance, texture features was suggested to have limited contribution to tumor classification.…”
Section: Discussionmentioning
confidence: 99%